Joint Ti-47 Al-2Cr-2Nb with a Ti-Ni braze alloy - Guedes, A. (2004)
Ti-47Al-2Cr-2Nb was joined by diffusion brazing using a Ti-Ni clad-laminated filler alloy. Brazing was performed in the temperature range of 1000 to 1200ºC for 10 min. The microstructure and the chemical composition of the interfaces were studied by scanning electron microscopy (SEM) and by energy dispersive X-ray scans (EDS), respectively. The reaction between the gamma-TiAl alloy and the liquid produced interfaces that should be essentially composed of alpha2-Ti3Al and Ti-Ni-Al intermetallics. When joints are brazed at 1150 and 1200ºC, a phase that should consist of gamma-TiAl is also detected at the interface.